The Role of Women's Equality in Government Programs: An Analysis from the Perspective of Qira'ah Mubadalah - Najib, Afifun; Sugianto, Sugianto; Setyadi, Yusuf (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
Women are frequently marginalised as a gender that receives less recognition in social life, particularly within patriarchal societies. In comparison to men, women experience inequality across various domains, both in societal contexts and within governmental structures. This phenomenon underscores the inherent injustices present in the dynamics between women and men. However, this does not imply that women's opportunities to assume leadership roles are entirely obstructed. This paper utilises the Qira'ah Mubadalah perspective, which emphasises the values of equality and justice for women, thereby advancing the role of equality between women and men. This research is qualitative in nature and employs an empirical-sociological approach. Primary data sources were obtained through field interviews, while secondary data were sourced from academic journals, implementation guidelines for the Family Hope Program, and relevant legislation. Data collection techniques included in-depth interviews conducted through direct fieldwork. The interview data were subsequently analysed using the Qira'ah Mubadalah framework. The findings indicate that women play a crucial role in the government's Family Hope Program (PKH). This is evident in the promotion of women's equality or reciprocity within PKH beneficiary families, the advancement of gender equity for women in the division of household responsibilities, and the reinforcement of equal relationships between men and women in the public sphere. Furthermore, this research contributes to enhancing public understanding and improving family law literacy. This paper may also pave the way for further exploration of the role of women's equality in other strategic government initiatives.